Picosecond laser ablation of polycrystalline CVD diamond. (November 2022) - Zhai, Jianchao; Zhang, Quanli; Zhu, Yandan
Highlights: The anisotropy of CVD diamond grains results in the nonuniform material removal; The thermal stress and temperature field is achieved to reveal the formed surface characteristics; Different surface microstructures are successfully fabricated on CVD diamond. Abstract: In the present work, the influence of the laser parameters on the surface characteristics of chemical vapor deposition (CVD) diamond are investigated. The temperature field, thermal stress field and phase field are established through simulation to explain the heat affected zone that results in the deterioration of diamond surface in the process of laser machining. The high temperature induced by laser and the local anisotropy of polycrystalline CVD diamond contribute to the inhomogeneous materials removal, which results in irregular gullies on the machined surface, and the thermal effect of picosecond laser leads to the gasification of a large amount of material, where less accumulated products in the processing area appear. The graphitization of diamond is induced in the groove, where less graphitization appears at the edge of the groove. In addition, the CVD diamond surface is oxidized and nitrided during the laser ablation. By comparing the surface morphology and the three-dimensional topography of the groove, a set of machining parameters are optimized to fabricate different surface microstructures on CVD diamond.